On the gravitomagnetic clock effect - Faruque, S. B. (Array, 2008)
Summary: We show that the whole of the gravitomagnetic clock effect in the orbit of a spinning test particle which is revolving round a spinning central massive astrophysical body can be calculated using a gravitational spin-orbit coupling potential which involves the two spins and the orbital angular momentum of the test particle